LncRNA CCAT1 facilitates the proliferation, invasion and migration of human laryngeal squamous cell carcinoma cells via the miR-218-5p/BMI1 - Jing Hong; Ali Hong; Houshu Tu; Zhichao Wan; Yuqiao Deng; Chengcheng Deng; Bo Tao; Yanjin Yu; Lanfei Zhou (PeerJ, 2022)
Long non-coding RNAs (LncRNAs) are vital in the treatment of laryngeal squamous cell carcinoma (LSCC). This study estimated the mechanism of lncRNA CCAT1 (CCAT1) in LSCC cells. The expression of CCAT1 in the human laryngeal mucosal epithelial cells (HLCs) and LSCC cells (Hep-2 and TU177) was detected. CCK-8 and Transwell assays were used to evaluate the cell proliferative, migrative, and invasive abilities, respectively. The subcellular localization of CCAT1 was verified by RNA-FISH and cytoplasmic isolation assays. The targeted relationship among CCAT1, miR-218-5p, and BMI1 was verified by dual-luciferase assay. Expressions of miR-218-5p and BMI1 were detected by RT-qPCR. Our results depicted that CCAT1 was highly-expressed in Hep-2 and TU177 cells. Silencing CCAT1 inhibited the proliferation, migration, and invasion of Hep-2 and TU177 cells. Mechanically, CCAT1 regulated the BMI1 expression by competitively binding to miR-218-5p as a competing endogenous RNA (ceRNA), and thus facilitated the growth of Hep-2 and TU177 cells. Downregulation of miR-218-5p or upregulation of BMI1 inhibited the inhibitory effect of silencing CCAT1 on Hep-2 and TU177 cell proliferation, invasion, and migration. In conclusion, our study elicited that lncRNA CCAT1 facilitated the proliferation, migration, and invasion of Hep-2 and TU177 cells by sponging miR-218-5p and regulating the downstream BMI1.